Preparation and Properties of Clay-Reinforced Epoxy Nanocomposites - Kusmono; M. W. Wildan; Z. A. Mohd Ishak (International Journal of Polymer Science)
The clay-reinforced epoxy nanocomposite was prepared by the polymerization method. The effect of clay addition on the mechanical properties of epoxy/clay nanocomposites was studied through tensile, flexural, impact strength, and fracture toughness tests. The morphology and tribology behavior of epoxy/clay nanocomposites were determined by X-ray diffraction (XRD) and wear test, respectively. The wear test was performed to determine the specific abrasion of the nanocomposites. In addition, the water absorption characteristic of the nanocomposites was also investigated in this study. XRD analysis indicated that the exfoliation structure was observed in the epoxy nanocomposites with 3 wt% of clay, while the intercalated structure was shown at 6 wt% of clay. It was found that the addition of clay up to 3 wt% increased the tensile strength, flexural strength, impact strength, and the fracture toughness. On the contrary, the presence of above 3 wt% of clay produced a reverse effect. It could be concluded that the best properties in mechanical, wear resistance, and water resistance were obtained for the epoxy nanocomposites containing 3 wt% of clay.